An assessment of the English and maths skills levels of prisoners in England (UCL Press, 2016)
Although the direct links between education and reducing recidivism in prisoners are problematic, there is little argument that education is a factor in promoting reintegration and rehabilitation. There is a current focus in prison education on education for employment, and yet there are no recent or unambiguous data about the skills levels of the prison population. The most often quoted figures are both 15 years out of date and deeply flawed in terms of their comparisons with the general population. This article sets out a new study that takes the mandatory initial assessments carried out on every new prisoner between August 2014 and July 2015 and compares them with the national Skills for Life survey conducted in 2011. This provides us with some hard facts about the English and maths skills of the past year's intake of prisoners. The conclusions argue that while the numeracy skills of prisoners are better than previously understood, the cohort has extremely poor literacy skills, and addressing these needs should be a priority for government.